DO FOREST CONCESSIONS BENEFIT EXTRACTIVIST COMMUNITIES? THE CASE OF THE JAMARI NATIONAL FOREST - Ansolin, Roni Djeison; Donicht Fernandes, Ana Paula; Bento, Marco Antônio; Timofeiczyk Junior, Romano; Hoeflich, Vitor Afonso; Alves da Silva, Samuel (Floresta, 2020)
The study aims to analyze the exploration potential of the main non-timber forest products in the Forest Management Unit number III by the communities around Jamari National Forest. Were used the açaí fruit and Brazilian nuts production data based on the sustainable management plan, as well the Brazilian nut crop production for 2015, 2016 and 2017 reported by traditional communities, "Américo Ventura" and "Linhas 113-119". The data were analyzed and interpreted using economic indicators. As the main results, the productive potential amount of açaí fruit and Brazilian nuts available for harvest in each annual crop is 426,86 tons and 124,13 tons, respectively, providing an estimate of annual income of R 79.794,64 and R 195.134,63, respectively. For Brazilian nuts, the annually demand raised by the community was approximately 8 tons, from 2015 to 2017. The amount harvested represents 44.77% of the productive capacity of the three units. In addition, the cost-benefit ratio indicates that for each Brazilian Real invested in production the producer receives, on average, R 5,72. The Brazilian nut extraction shows to be an interesting activity in terms of production and economic value in both communities, presenting a net annual gain of R 1.812,108 per collector, for a total group of 50 extractivists residing in the communities “Américo Ventura” and “Linhas 113-119”, between 2015 to 2017. Thus, it is concluded that there is a great potential for exploration of these products in partnership with the concession forest, contributing to the sustainable development of extractivist communities.